Direct Torque Control for Open-End Winding Interior Permanent Magnet Synchronous Motor with multi-level hysteresis bandgap - Yoon, Tae Yong; Lee, Hyung Woo; Lee, Kyo Beum (SCEMS 2022 - 2022 IEEE 5th Student Conference on Electric Machines and Systems, 2022)
This paper proposes improved direct torque control (DTC) method to drive an open-end winding interior permanent magnet synchronous motor (OEW-IPMSM). DTC provides fast response properties with simple control algorithm. In conventional DTC, torque and stator magnetic linkage flux are controlled by single bandgap that makes authorizing same magnitude of voltage vector. The single bandgap makes the variance of torque or stator magnetic linkage flux to be fixed, difficult to use in a wide range of speeds. In this paper, to drive wide speed regions, multi-level torque bandgap is applied by using dual inverters that has voltage vectors with three different magnitudes. When the variance of the torque is required to follow the reference, proposed method selects the voltage vector that have appropriate magnitude. The validity of the proposed DTC for OEW-IPMSM is verified by the simulation results.
Keywords: Direct torque control; Dual inverters; Interior permanent magnet synchronous motor; Linkage flux; Multi bandgap; Multilevels; Open-end winding IPMSM; Open-end windings; Voltage vectors; Wide speed region; direct torque control; dual inverter; multi bandgap; open-end winding IPMSM; wide speed regions